(untitled) (RT. A Journal on Research Policy and Evaluation, 2015)
The Recruitment of professors and researchers by Italian public Universities is limited not only by the financial constraints imposed by National laws, but also by the conversion of the financial resources into positions according to a rule established a few years ago by the Ministry of Education and expressed by the so-called “Punto Organico” (P.O.).The origin of the notion of P.O. is traced back to some statistical studies performed more than a decade ago . Its subsequent application to university recruiting follows from a sequel of administrative actions taken by the Ministry but it is not based on an explicit (and formally required) legal formulation. The recent structural evolution of the university system and some changes in the legislation have further weakened the justification for such a constraint. An alternative (and legally consistent) mechanism for keeping under control the projected expenses for personnel is proposed